Du seisch wo düre (DSWD)/It is your decision - a programme of health promotion and prevention at school for adolescents - Messerli, Maria; Heinz, Bolliger-Salzmann (Acta Biomedica Atenei Parmensis, 2014)
Du seisch wo düre (DSWD means, “It is your decision” in Bernese German). This proven, scientifically sound and regularly evaluated component of health promotion and prevention has, for over 20 years, been appreciated by adolescents, aged 14-16 years. This resource-oriented programme at school (“Sekundarstufe I” in Switzerland) helps students answer current questions about vital issues and develop their own problem-solving strategies. The programme enhances life skills, independence and self-esteem in participating adolescents, and strengthens social cohesion within circles of peers. Improved social competence also improves the classroom interaction and the climate of the school. Specially-trained external facilitators assist participants. Faciliators can use proven instruments and methods to moderate the discussions. DSWD also contributes to secondary prevention (for example, preventing addiction and violence). Since 2009, the concept has been extended to target vulnerable adolescents, and programme evaluations have demonstrated good results. zWäg!, a new programme based on the same concept as DSWD, addresses the needs of young adults in work preparatory schools and in work settings. For reasons of space, this article discusses only DSWD.